Demographic Change and Intergenerational Justice - Tremmel, Joerg Chet (Springer, 2017)
Intergenerational justice has been achieved if the opportunities of the members of the next generation to fulfill their needs are better than those of the members of the preceding generation. For this, each generation ought to leave for the next generation an amount of resources is at least equal to its own amount (...)